ANALISIS TOTAL FENOL PADA BERBAGAI FORMULASI REBUSAN KULIT SALAK BALI SIBETAN KARANGASEM SEBAGAI MINUMAN FUNGSIONAL - Wayan Merta (Jurusan Analisis Kesehatan, Poltekkes Kemenkes Denpasar, 2016)
Abstract Background: Snakefruit’s bark that only so far as waste, can be processed into a functional beverage is good for health. Snakefruit’s bark contains phenolic compounds which are natural antioxidants in fruits. Objective: The purpose of this study is to determine the total phenol levels and sensory value of stew salak bali sibetan karangasem’s bark in various formulations as functional beverage. Methods: Analysis of total used spectrophotometric method with Folin-Ciocalteu phenol reagent and gallic acid standard. It also performed the water content analysis used thermogravimetry method. Result: Salak Bali Sibetan’s bark have average water content 24.1872±0.036%wb. The results of total phenol analysis showed that 2, 10, 20, 30, 40 gram of Salak Bali’s bark with 200 ml water are: 10,84±0,587; 13,79±0,756; 12,19±0,205; 12,02±0,268; 10,57±0,389 mg/L GAE respectirely. Conclusions: The highest total phenol content is (10g/200ml) formulation, and also supported by a sensory test showed that a majority of panelist also prefer that formulation because has good colour, flavor and smell. Keywords : Salak Bali’s Sibetan bark, total phenol, Folin-Ciocalteu.